Application of Ultrasonic Waves on Maintaining Freshness of Tilapia Fillet - Ruddy Suwandi; Agoes Mardiono Jacoeb; Maya Sofia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Fish fillet is one of fisheries products that easily deteriorated; hence handling techniques are needed to maintain the freshness. Ultrasonic wave have been widely applied to some of food products for maintaining freshness through microbial inactivation, however the ultrasonic application to fisheries products has not been reported. The purpose of this study was to analyze the effect of ultrasonic wave on fish freshness. The stages of the study were sample preparation, sonication, freshness parameters examination and histology observation. Ultrasonic wave did not affectthe organoleptic value and the TVB, but affected the pH value and the TPC. The sample in which the TPC value was found significantly different, were further observed after 48 and 96 hours storage. The result showed that the TPC value of sonicated sample for 9 minutes was lower to that of without sonication. Histology analysis showed, however, sonication made the structure of muscle fiber less compact and deformation of myomer was found. Keyword: Fillet, freshness, histology, nile tilapia, sonication, ultrasonic wave